Optimization of phytase production by Penicillium funiculosum NRC467 under solid state fermentation by using full factorial design - Awad, G.; Elnashar, Magdy; Danial, E. (2011)
Nine substrates were investigated for phytase production by Penicillium funiculosum NRC467 fine particles of crushed fava bean has been selected as the best substrate using solid state fermentation (SSF). The SSF conditions were optimized by using one-variable-at-a-time (OVAT) strategy. Penicillin G has been used to enhance phytase production instead of the traditionally used Tween 80 and Triton X100. 3 3 Full factorial design of response surface methodology was applied to describe the relationship between the tested variables, cane molasses, penicillin G, pH and phytase activity. The results showed that the maximum phytase activity of 392.4 U/g ds was attained when concentrations of both cane molasses and penicillin G were 20% (w/v) and 40 U/g ds, respectively at fermentation medium of pH 8. This result represent an improvement in phytase production of 8.2 folds when compared to that previously obtained using the basal medium under the same cultivation conditions. The generated model was found to be very adequate for phytase production (95% accuracy) as the experimental value was 392.4 U/g ds compared to 401 U/g ds for the predicted value. In brief, the use of fava bean and penicillin G for production of phytase are novel and will open new way for researchers to discover and explore this arena. © IDOSI Publications, 2011.